2011
DOI: 10.1177/1470320310391332
|View full text |Cite
|
Sign up to set email alerts
|

Highly purified human peripheral blood monocytes produce IL-6 but not TNFα in response to angiotensin II

Abstract: Hypothesis: Monocytes produce pro-inflammatory cytokines in response to Angiotensin II (AngII). Introduction: AngII has been suggested by many to be pro-inflammatory and likely to contribute to the migration of leukocytes in patients with cardiovascular conditions. Materials and methods: Monocytes were purified from peripheral blood mononuclear cells (PBMCs) by negative selection using antibodies conjugated to magnetic beads. Detection of CD14 + and AT 1 R expression was achieved by double-labeling flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…IMo also called M1 monocytes is a subtype of monocytes thought to be an important cellular source of IL-6 [21,22]. We found that CAWS injection resulted in mobilization of iMo into the periphery, as indicated by over a two-fold increase in the proportion of iMo in the blood and spleen of Ccr2 +/+ CAWS-injected compared to PBS injected mice (Figure 5E and F).…”
Section: Resultsmentioning
confidence: 79%
“…IMo also called M1 monocytes is a subtype of monocytes thought to be an important cellular source of IL-6 [21,22]. We found that CAWS injection resulted in mobilization of iMo into the periphery, as indicated by over a two-fold increase in the proportion of iMo in the blood and spleen of Ccr2 +/+ CAWS-injected compared to PBS injected mice (Figure 5E and F).…”
Section: Resultsmentioning
confidence: 79%
“…Endogenous ANG II increased T-cell activation, leading to production of TNF-α [ 60 ] and blocking of ACE was found to increase Treg population in the spleen [ 61 ]. Additionally, ANG II increased IL-6 release in monocytes [ 62 ] and the increased IL-6 in CHC mice might affect to Treg population in CHC mice. It has been reported that IL-6 was required for overcoming Treg suppressive function with some other cytokines [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…45 Briefly, PBMCs were separated from blood on a gradient (Histopaque-Ficoll; Sigma-Aldrich, Munich, Germany), washed twice at 1500 rpm for 10 minutes to remove platelets, and live cells were counted with a hemocytometer (MSUM Biochem and Biotech, Moorhead, MN) using the Trypan Blue exclusion method. Total blood monocytes, including both subsets of CD14þþCD16-and CD14þCD16þ monocytes were isolated using a negative selection kit (EasySep, Stemcell Technologies, Vancouver, Canada) according to manufacturer's instructions.…”
Section: Qpcrmentioning
confidence: 99%